Reconstruction of Ta’dib Concept: A Critique and Redefine of Syed Muhammad Naquib al-Attas’s Thought - Dardiri, Muhammad Amiruddin; Baidhawy, Zakiyuddin; Supardi, Supardi (EDUKASIA, 2026)
Syed Muhammad Naquib al-Attas’s concept of ta’dib as an Islamic educational framework has faced various epistemological, pedagogical, and practical critiques. These critiques do not indicate a weakness in the philosophical substance of ta’dib itself; rather, they reveal the absence of an operational formulation capable of bridging Al-Attas’s philosophical vision with the practical demands of contemporary Islamic education. This study aims to reconstruct the concept of ta’dib to make it more operational and applicable as a paradigm for Islamic education curriculum. This study employed Paul Ricoeur’s philosophical hermeneutic approach through three stages (distanciation, critical interpretation, and appropriation). The findings showed the philosophical substance of ta’dib is internally coherent and remains valid despite existing critiques. The novelty of this study lies in transforming ta’dib from a philosophical-normative concept into a structured conceptual-operational model, by redefining ta’dib as a conscious and gradual process of internalizing justice that integrates spiritual, intellectual, and moral dimensions, and systematically translating it into four core curriculum components: objectives, content, methods, and assessment. Thus, this study not only offers a theoretical reinterpretation, but also provides a new implementable framework for operationalizing ta’dib as a comprehensive alternative paradigm of Islamic education that is relevant to contemporary educational challenges.